GENERALIZATION OF "FERMAT'S LAST THEOREM" THE SUM OF THE DEGREES OF INDEPENDENT AND UNEQUAL INTEGERS - Loshkarev, M. O. (Science and Transport Progress, 2007)
«The great theorem the Pherma» for the sum of any number of composed extents of integers is in-process generalized.